The Essential Oils of the Aerial Parts of Two Hypericum (H. pseudolaeve Robson and H. thymbrifolium Boiss. & Noe) (Guttiferae) Species from Turkey - Bagci, E.; Yuce, E. (Taylor & Francis Ltd, 2010)
In this study, essential oil composition of two Hypericum L. (Hypericum pseudolaeve Robson and H. thymbrifolium Boiss. & Noe) species grown in Turkey were determined by using GC and GC-MS system. The essential oils obtained by hydrodistillation from the aerial parts of plants. Forty-five compounds were identified in the essential oils of H. pseudolaeve; trans-caryophyllene (23.92%), delta-limonene (11.19%), alpha-cadinol (10.67%), caryophyllene oxide (7.96%), alpha-pinene (5.76%), spathulenol (5.21%) and beta-selinene (3.02%). Fifty-four components were identified in H. thymbrifolium oil, alpha-pinene (51.31%), undecane (4.94%), germacrene D (4.70%), beta-pinene (3.68%), beta-myrcene (3.30%), spathuleneol (2.92%) and naphthalane (1.88%) were determined as the main constituents. Monoterpenes were shown to be the main group of the H. thymbrifolium, while the H. pseudolaeve were more rich in sesquiterpenes. The results have supplied contributions on the usability of oils as renewable resources and chemotaxonomy of plants.
Keywords: Hypericum; Guttiferae; GC-MS; Essential oil; trans-caryophyllene; alpha-pinene; chemotaxonomy